Pemanfaatan Tanah Kas Desa oleh Pemerintah Desa dalam Meningkatkan Perekonimian Masyarakat di Desa Sungai Sayang Kecamatan Sadu - Noferiadin Noferiadin; Daud Daud; Siti Fatimah; Haeran Haeran; Erwina Kartika Devi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the form of utilization of village treasury land (TKD) carried out by the Sungai Sayang Village Government and how the utilization of TKD contributes to improving the community's economy. Village treasury land is a village asset that can be utilized to support development and community welfare if managed properly. This study uses a qualitative approach with a descriptive method. Data collection techniques are carried out through in-depth interviews with the Village Head, Village Secretary, Head of the Village Consultative Body (BPD), and two farmers who are directly involved in the management of village treasury land. The results of the study showed that the utilization of village land in Sungai Sayang Village was carried out by planting oil palms which were managed directly by the village government in collaboration with the local community. Unlike in several other villages that rent village land, in Sungai Sayang Village the land is managed collectively by residents, so that the benefits can be felt directly by the community. The cooperation system is carried out through mutual cooperation and the harvest is divided according to each person's contribution. This utilization has a positive impact on the community's economy, especially for residents who do not have permanent jobs, because they can earn income from the oil palm harvest.